2015
DOI: 10.4103/0976-3147.143214
|View full text |Cite
|
Sign up to set email alerts
|

Orbital extension of trigeminal schwannoma

Abstract: Schwannomas, also known as neurilemmomas, are benign peripheral nerve sheath tumors. Trigeminal schwannomas are rare intracranial tumors. Here, we report a 35-year-old female presenting with an axial proptosis of right eyeball with right-sided III, IV and VI cranial nerve palsy. Her best corrected visual acuity in the right eye was perception of light absent and in the left eye was 20/20. MRI scan revealed a large right-sided heterogeneous, extra-axial middle cranial fossa mass that extended to the intraconal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…These tumors are usually encapsulated and non invasive in nature and has minimum effect on orbital structure [7,8]. Sometimes orbital schwannoma can affect the eye by mechanical compression which can cause globe displacement, diplopia and proptosis [9][10][11]. Study conducted by Singh M., et al found that 69% of the orbital schwannoma were unilateral with preponderance for the right orbit [12], which correlates with our report.…”
Section: Discussionsupporting
confidence: 84%
“…These tumors are usually encapsulated and non invasive in nature and has minimum effect on orbital structure [7,8]. Sometimes orbital schwannoma can affect the eye by mechanical compression which can cause globe displacement, diplopia and proptosis [9][10][11]. Study conducted by Singh M., et al found that 69% of the orbital schwannoma were unilateral with preponderance for the right orbit [12], which correlates with our report.…”
Section: Discussionsupporting
confidence: 84%
“…For intra and interdural tumors, cranial base approaches are preferred, since they allow a better trigeminal exposure, minimizing cerebral retraction [16,17]. On the other hand, in those tumors of V1, the temporopolar approaches are the ones of choice, while those originating in V2 and V3 infratemporal resection is preferred, allowing the exposure of the foramen ovale, the pterygopalatine ganglion and the infratemporal fossa [4,18].…”
Section: Discussionmentioning
confidence: 99%
“…These patients usually present with slowly progressive proptosis, diplopia, decrease extraocular movement, and sometimes with vision loss if the tumor directly compresses the optic nerve or secondarily due to raised intracranial pressure. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Intraorbital extension of trigeminal schwannoma is even rarer. [ 4 ] These patients usually present with painless slowly progressive proptosis with or without vision loss. We are reporting such a rare case of solid cystic trigeminal schwannoma with intraorbital extension.…”
Section: Introductionmentioning
confidence: 99%